If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) = -12 Reorder the terms: 2(-7 + x) = -12 (-7 * 2 + x * 2) = -12 (-14 + 2x) = -12 Solving -14 + 2x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2x = -12 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = -12 + 14 2x = -12 + 14 Combine like terms: -12 + 14 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 24x=9x+210 | | 8(a+9)=99.2 | | 9g-14=2a | | 7x^2+16x-13=11-6x | | 42=5c-5 | | =x^2+x-6 | | 7x-0.4=6x-0.6 | | 3x-1=3.2 | | 111-7x=20x+18 | | 9x=87.3 | | 9x-180=-45 | | 11z-5=9z+1 | | (5d-6)(-4d+9)= | | 4a+6b+3+9a+2b= | | 2(-3x+5)-8=-x+17 | | 12x+3=3x+57 | | =3x^2+13x+4 | | 6-9x=28-16x | | 18y=12y^2 | | h(x)=3x^2+13x+4 | | 7(x-8)=-35 | | 9(x+7)=99 | | k^2+8k=105 | | 0=6x^2+6x-36 | | 2x^2-6x-36=0 | | 12-8x=81-29x | | 6x-2=8x+4 | | h(t)=-16t^2+63t+4 | | 5+2(x+3)=10-(3x-13) | | P-167=321 | | 180=j-24 | | 125-2x=5x+20 |